Nilai Ekonomi Penegakkan Disiplin Lalu Lintas Di Lampu Merah Bubulak, Kota Bogor Terhadap Pendapatan Daerah (Benchmarking Kasus Di Malaysia) - Falatehan, A. Faroby; Siswanto, Adrianus Dwi (Warta Penelitian Perhubungan, 2012)
ABSTRACTTraffic violations is still not taken seriously in Indonesia, 111~for hmately gafe a big impact 011 regional income. This study discused about the impact tl1e implementation of traffic discipline on local income based on Law No. 21 of 2009. This study approaches the number of violations associated witli the penalties for violations. Observations was conducted in the morning, afternoon and evening for 2 hours which is a solid hour passengers. While the observations made to the vehicle who commits an offense within that period. Further estimated the average per day of violation for the incident and then calculated the amount of the fine revenue in certain periods. The results of the study found that the estimate of receipts relatively large fines which indicates the first violation ever occurred that indicate the presence of non-compliance of traffic regulations. The second penalty is the appropriate option to create a deterrent effect on the offense. Fines provide benefits to local government as a source of income as well as educate tire publictransportation drivers to obey the rules. In Malaysia, a fine policy can be effective because the workers are very disciplined and a beingof the rules. On the other hand it is designed with a simple mechanism in which fines violators will pay the fine at the time of extending the driver's license. This approach is effective for improving adherence offenders while keeping the fine revenue obviously go into the treasuryaccount.Key Words: traffic violations, discipline, Law No. 21 of 2009, revenues